Les constructions sociales de la sexualite - Bozon, Michel; Leridon, Henri (Population (French Edition), 1993)
Keywords: 1900-1999; approches et analyses; cours; discipline; premier cycle; production des savoirs; périodes historiques; rapports sociaux de sexe; sciences humaines; sciences sociales; sex1183; sexologie; sexualité; thématiques; épistémologie

Mais à quoi sert une épistémologie des rapports sociaux de sexe? - Combes, Danièle (Sexe et genre. De la hierarchie entre les sexes, 1991)
S’inscrivant dans le mouvement des études féministes qui ont marqué les années quatre-vingt, cet ouvrage réunit les différents points de vue de femmes universitaires engagées dans des champs de recherches aussi divers que la biologie, le droit, la linguistique. Partant de l’examen critique de la distinction sexe et genre, elles analysent les mécanismes qui assurent le maintien de la domination masculine et font progresser la réflexion sur les déterminants de la subordination des femmes.
Keywords: 1900-1999; 1980-1989; approches et analyses; classe sociale; cours; discipline; europe; fem1000; france; histoire et politique; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; épistémologie

Whose science? Whose knowledge?: Thinking from women's lives - Harding, Sandra G. (Science question in feminism, 1991)
Sandra Harding here develops further the themes first addressed in her widely influential book, The Science Question in Feminism, and conducts a compelling analysis of feminist theories on the philosophical problem of how we know what we know.Following a strong narrative line, Harding sets out her arguments in highly readable prose. In Part 1, she discusses issues that will interest anyone concerned with the social bases of scientific knowledge. In Part 2, she modifies some of her views and then pursues the many issues raised by the feminist position which holds that women's social experience provides a unique vantage point for discovering masculine bias and and questioning conventional claims about nature and social life. In Part 3, Harding looks at the insights that people of color, male feminists, lesbians, and others can bring to these controversies, and concludes by outlining a feminist approach to science in which these insights are central. "Women and men cannot understand or explain the world we live in or the real choices we have," she writes, "as long as the sciences describe and explain the world primarily from the perspectives of the lives of the dominant groups."Harding's is a richly informed, radical voice that boldly confronts issues of crucial importance to the future of many academic disciplines. Her book will amply reward readers looking to achieve a more fruitful understanding of the relations between feminism, science, and social life.
Keywords: approches et analyses; cours; discipline; fem1000; point de vue situé; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; épistémologie

The science question in feminism - Harding, Sandra G. (Cornell University Press, 1986)
Can science, steeped in Western, masculine, bourgeois endeavors, nevertheless be used for emancipatory ends? In this major contribution to the debate over the role gender plays in the scientific enterprise, Sandra Harding pursues that question, challenging the intellectual and social foundations of scientific thought.Harding provides the first comprehensive and critical survey of the feminist science critiques, and examines inquiries into the androcentricism that has endured since the birth of modern science. Harding critiques three epistemological approaches: feminist empiricism, which identifies only bad science as the problem; the feminist standpoint, which holds that women's social experience provides a unique starting point for discovering masculine bias in science; and feminist postmodernism, which disputes the most basic scientific assumptions. She points out the tensions among these stances and the inadequate concepts that inform their analyses, yet maintains that the critical discourse they foster is vital to the quest for a science informed by emancipatory morals and politics.
Keywords: approches et analyses; cours; discipline; fem1000; point de vue situé; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; épistémologie